TECHNOLOGICAL APPROACH TO THE HARMONIOUS DEVELOPMENT OF THE STUDENT’S PERSONALITY IN THE EDUCATIONAL PROCESS - THE DRIVING FORCE GROWTH OF TEACHER’S CREATIVE POTENTIAL - Reva Ю.В. (Pedagogy of Higher and Secondary Education, 2022)
This article deals with the harmonic development of a student’s personality with the help of technological approach in the process of studying the success of which is based on the pedagogical skill.